Hubungan Tingkat Kepatuhan Minum Obat Antihipertensi terhadap Tekanan Darah pada Lansia di Klinik Pratama Rawat Inap Ronggo Husada Malang - Natasa Nabila Mauluddia (JURNAL RISET RUMPUN ILMU KESEHATAN, 2026)
Hypertension in the elderly requires long-term treatment to prevent cardiovascular consequences. Adherence to antihypertensive medication is crucial for blood pressure management. Adherence to antihypertensive medication is a crucial aspect in hypertension management. Poor adherence can lead to uncontrolled blood pressure, thereby increasing the risk of cardiovascular problems, including stroke, myocardial infarction, and heart failure. This study aims to determine the correlation between adherence to antihypertensive medication and blood pressure in the elderly at the Ronggo Husada Primary Inpatient Clinic in Malang. This study used a cross-sectional design. The cohort consisted of 52 geriatric patients with hypertension who consistently visited the Ronggo Husada Primary Inpatient Clinic in Malang. The sample consisted of 40 patients. The sampling method used was purposive sampling. Research factors included medication adherence and blood pressure. Data collection was conducted through a questionnaire. This study was conducted at the Ronggo Husada Primary Inpatient Clinic in Malang on November 6, 2025. Data processing used the Chi-square test. The analysis included univariate and bivariate analyses, using the Chi-square test. The results showed that more than 50% of elderly participants demonstrated moderate adherence to antihypertensive medication (18 individuals (45%). Nearly 50% of elderly participants suffered from stage I hypertension (14 individuals (35%), and stage II hypertension (11 individuals (27.5%). Statistical analysis using the Chi-square test showed a significant correlation between adherence to antihypertensive medication and blood pressure in the elderly, with a p-value of 0.000, which is below the alpha threshold of 0.05 (5%). Elderly individuals who demonstrated strong adherence had better blood pressure regulation compared to those with poor adherence. These results emphasize the importance of adherence to therapy in the management of hypertension in the elderly.